(untitled) (The Research of Medical Science Review, 2025)
This case study details a patient experiencing depressed symptoms and significant stress associated with public speaking. The patient exhibits anxiousness, pallor, and aversion to delivering presentations. He was apprehensive about committing mistakes and facing humiliation before his peers. These emotions have prompted avoidance behaviors, such as missing classes that necessitate presentations. The patient's self-esteem is compromised, and he expressed feelings of despair and episodes of crying as a result. This instance exemplifies the effect of public speaking fear on an individual's mental health and daily functioning. The therapy of social anxiety disorder necessitates the application of behavioral methods to aid patients in acquiring new cognitive and behavioral approaches in social situations. Systematic desensitization aims to alleviate anxiety and enhance the patient's comfort and confidence in feared or avoided social situations. It aided patients in confronting negative attitudes and managing social interactions.